Magnetic pulse controlled microstructure development in Co49Ni21Ga30 single crystals. Issue 16 (2nd November 2018) - Gerstein, Gregory; Firstov, Georgiy; Chumlyakov, Yuri; Krooß, Philipp; Niendorf, Thomas; Dalinger, Andrej; Maier, Hans Jürgen
ABSTRACT: A pulsed magnetic field (MF) up to 0.6 T leads to the generation of fine microstructure through the change in the dynamics of the interaction process between the MF and the magnetic- and microstructure in Co49 Ni21 Ga30 magnetic shape memory alloy single crystals. This paper addresses the impact of pulsed and permanent MF on the transformation behaviour in Co49 Ni21 Ga30 . A pulsed MF can result in different microstructural accommodation processes in stress-induced martensite, as compared to an application of a mechanical stress or permanent MF. In a pulsed MF, the development of new nano-twin systems in the martensitic structure of the CoNiGa alloy and the formation of fine magnetic domains at the microscale are observed.